2020
DOI: 10.1016/j.psj.2019.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profiles and health lipid indices in the breast muscles of local Polish goose varieties

Abstract: The aim of this study was to evaluate the fatty acid profile and health lipid indices of meat from 3 Polish local goose varieties (Romanian–RO, Pomeranian–PO, and Subcarpathian–SB) and the commercial cross White Kołuda goose (W31). Birds were fed ad libitum with the same complete feeds until 17 wk of age. The geese (n = 72) with body weight close to the arithmetic mean in particular flock were fasted for 12 h and slaughtered in an experimental slaughterhouse (18 females in each flock). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 43 publications
8
87
4
Order By: Relevance
“…From the perspectives of human health, healthy animal products can be characterized by low AI and TI and a high h/H ratio. Generally, the desired AI and TI recommended for human consumption are less than 0.5 and 1.0, respectively [29]. In this study, the breast meat showed AI and TI of 0.42-0.43 and 0.60-0.82, and the thigh meat showed AI and TI of 0.42-0.44 and 0.62-0.80 with MA supplementation, which were within the recommended ranges.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…From the perspectives of human health, healthy animal products can be characterized by low AI and TI and a high h/H ratio. Generally, the desired AI and TI recommended for human consumption are less than 0.5 and 1.0, respectively [29]. In this study, the breast meat showed AI and TI of 0.42-0.43 and 0.60-0.82, and the thigh meat showed AI and TI of 0.42-0.44 and 0.62-0.80 with MA supplementation, which were within the recommended ranges.…”
Section: Discussionsupporting
confidence: 67%
“…AI and TI are vital parameters indicating the potential for stimulating platelet aggregation, and the h/H ratio is associated with cholesterol metabolism [29]. From the perspectives of human health, healthy animal products can be characterized by low AI and TI and a high h/H ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Fats with the PUFAs/SFAs ratio of greater than 0.45 are recommended for human consumption to minimize the risk of CVD and other chronic diseases [ 12 ]. In the present study, PUFAs/SFAs ratios ranged from 0.89 (black shrimp waste) to 1.70 (red shrimp waste) ( Table 5 ), which falls within the recommendations.…”
Section: Resultsmentioning
confidence: 99%
“…The fatty acid profile was used to determine several nutritional parameters of lipids, including ratios of PUFAs/saturated fatty acids (SFAs), PUFAs/monounsaturated fatty acids (MUFAs), and hypocholesterolemic (h)/hypercholesterolemic fatty acids [ 11 , 12 ]. Furthermore, the atherogenic index (AI) [ 11 ], and thrombogenic index (TI) [ 13 ] were calculated as the following equations: …”
Section: Methodsmentioning
confidence: 99%
“…Atherogenic index and TI are vital parameters indicating the potential for stimulating platelet aggregation, which defined as the relationships between proatherogenic FA and antiatherogenic FA and relationships between prothrombogenetic FA and antithrombogenetic FA, respectively ( Wołoszyn et al., 2020 ). From the perspectives of human health, the AI and TI recommended for human consumption are less than 0.5 and 1.0, respectively ( Wołoszyn et al., 2020 ). In this study, the yolks showed AI and TI of 0.37–0.41 and 0.69–0.73, which were within the recommended ranges.…”
Section: Resultsmentioning
confidence: 99%